Factors affecting intention to leave among millennial employees at Yamaha Electronics Manufacturing (M) Sdn. Bhd. - Nurul Khairunnisa, Muhashamsani (2018)
The purpose of this study was to determine the relationship between job satisfaction, pay satisfaction and work environment towards intention to leave among the millennial employees of Yamaha Electronics Manufacturing (M) Sdn Bhd which is a manufacturing organization in Ipoh, Perak. Three independent variables representing were namely job satisfaction, pay satisfaction and work environment have been selected for this study while intention to leave which is the dependent variable. The millennial employees from Yamaha Electronics Manufacturing (M) Sdn Bhd which is a manufacturing organization in lpoh, Perak have been selected as a target population. A I total of 230 questionnaires were distributed randomly to the millennial employees of Yamaha Electronics Manufacturing (M) Sdn Bhd from age range of 24 - 35 years old and only 220 sets were returned and usable. Correlation and Multiple Regression test were used to analyse the data. Research findings revealed that job satisfaction were significant with intention to leave (β==-0.343, t==-5.298, p==0.000) was found to have the greatest influence; while pay satisfaction and work environment was not significant with intention to leave.